A New Approach to Desirable Responding: Multidimensional Item Response Model of Overclaiming Data. Issue 3 (May 2023) - Jin, Kuan-Yu; Paulhus, Delroy L.; Shih, Ching-Lin
A variety of approaches have been presented for assessing desirable responding in self-report measures. Among them, the overclaiming technique asks respondents to rate their familiarity with a large set of real and nonexistent items (foils). The application of signal detection formulas to the endorsement rates of real items and foils yields indices of (a) knowledge accuracy and (b) knowledge bias . This overclaiming technique reflects both cognitive ability and personality. Here, we develop an alternative measurement model based on multidimensional item response theory (MIRT). We report three studies demonstrating this new model's capacity to analyze overclaiming data. First, a simulation study illustrates that MIRT and signal detection theory yield comparable indices of accuracy and bias—although MIRT provides important additional information. Two empirical examples—one based on mathematical terms and one based on Chinese idioms—are then elaborated. Together, they demonstrate the utility of this new approach for group comparisons and item selection. The implications of this research are illustrated and discussed.